Physical activity as a component of depression therapy: Narrative Review - Niedziela, Natalia; Woźnicka, Antonina; Trzeciak, Zuzanna; Filippoto, Oliwia; Klincewicz, Julia; Denisewicz, Natalia; Fornalski, Emil; Klincewicz, Jan; Kleiber, Maja; Kopeć, Stanisław; et al. (Quality in Sport, 2026)
Introduction and purpose: Depression is a common and disabling mental disorder associated with impaired quality of life, reduced social and occupational functioning, and increased mortality. Growing evidence indicates that lifestyle-related factors, including physical activity, may influence both the risk and course of depressive disorders. The aim of this narrative review is to evaluate the current evidence regarding the role of physical activity as a supportive component in the prevention and treatment of depression. Brief description of the state of knowledge: The available literature suggests that exercise may reduce depressive symptoms through several interacting biological and psychosocial mechanisms. These include modulation of neurotransmitter systems, improvement of neuroplasticity and brain-derived neurotrophic factor activity, regulation of the hypothalamic-pituitary-adrenal axis, and reduction of chronic low-grade inflammation. Aerobic exercise remains the most widely studied modality, but resistance training, combined exercise programs, yoga, and mind-body interventions have also shown beneficial effects in various populations. Evidence from cohort studies additionally supports a preventive association between regular physical activity and lower risk of incident depression. Summary: Physical activity should not be considered a universal replacement for pharmacotherapy or psychotherapy, particularly in severe depression. However, it may represent a valuable adjunctive strategy within comprehensive and individualized mental health care. Further research is needed to define optimal exercise parameters, improve adherence, and clarify the mechanism of action of physical activity on patients with depression in different clinical populations.